(untitled) (Interdisciplinary Studies Journal, 2026)
This study aimed to analyze how artificial intelligence (AI) can be incorporated into teaching practices in Adult and Youth Education (EJA) to promote meaningful, inclusive, and critical learning. Conducted with a 1st Segment EJA I class at a public school on the outskirts of Fortaleza, the study adopted a qualitative approach grounded in action research, emphasizing active participation of the learners and recognizing their life experiences, prior knowledge, and cultural repertoires as central elements of the educational process. The activity involved retrieving affective memories related to June festivities, producing handmade invitations, and later using digital tools such as Canva and ChatGPT to create graphic versions, exercising authorship, critical review, and collaborative engagement. Teacher mediation guided the use of AI in an ethical, critical, and intentional manner, enabling the development of multiple literacies, digital competencies, and creative expression. The results indicated that the integration of traditional practices with emerging technologies strengthened cultural belonging, valued learners’ life trajectories, and expanded opportunities for meaningful learning. It is concluded that the intentional use of AI in EJA constitutes a pedagogical strategy capable of fostering inclusion, critical thinking, and learner protagonism.